THE IMPORTANCE OF CULTURAL UNDERSTANDING IN TRANSLATION - Bakhronova Barchinoy (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article talks about the importance of cultural understanding in translation and gives some important aspects of cultural communication in translation.